Surface modification of a dental Ti by blasted coating of bio-active calcium phosphate - Jung, H. Y.; Lee, S. H.; Byeon, J. W.; Doh, J. M.; Hong, K. T.; Lim, H. N. (ECO-MATERIALS PROCESSING AND DESIGN VIII, 2007)
An attempt was made to coat bio-active calcium phosphate on a titanium substrate by room temperature blasted-coating process as an alternative for conventional thermal spray or ion beam-assisted coating techniques. Thickness, surface roughness, crystallinity, and Ca and P-dissolution behavior of the coated layer were investigated as a function of pressure and time of the blasted coating process. The blasted coating process offered comparable coating characteristics with those of conventional techniques, including a thickness of 1.3 mu m similar to 6.3 mu m, and a surface roughness of 1.5 similar to 2.3 mu m. Furthermore, the blasted coating layer showed higher crystallinity and more favorable dissolution behavior (i.e., constant and long-lasting release of Ca and P) than those of the convention thermal processes. Based on the comparable or superior characteristics of the blasted coating process at room temperature, it was suggested as a useful technique for calcium phosphate coating on Ti-based medical device.